Developmentally Regulated Modulation of Lumbar Motoneurons by Metabotropic Glutamate Receptors: A Cellular and Behavioral Analysis in Newborn Mice - Quilgars, Camille; Cazalets, Jean-René; Bertrand, Sandrine S. (Frontiers in Cellular Neuroscience, 2021)
The present study explores the impact of metabotropic glutamate receptor (mGluR) activation on activity-dependent synaptic plasticity (ADSP) and the intrinsic membrane properties of lumbar motoneurons (MNs) using a combination of biochemical, pharmacological, electrophysiological and behavioral techniques. Using spinal cord slices from C57BL/6JRJ mice at two developmental stages, 1-3 and 8-12 postnatal days (P1-P3; P8-P12, respectively), we found that ADSP expressed at glutamatergic synapses between axons conveyed in the ventrolateral funiculus (VLF) and MNs, involved mGluR activation. Using specific agonists of the three groups of mGluRs, we observed that mGluR stimulation causes subtype-specific and developmentally-regulated modulation of the ADSP and synaptic transmission at VLF-MN synapses as well as the intrinsic membrane properties of MNs. RT-qPCR analysis revealed a downregulation of mGluR gene expression with age in the ventral part of the lumbar spinal cord. Interestingly, the selective harvest by laser microdissection of MNs innervating the Gastrocnemius and Tibialis anterior muscles unraveled that the level of Grm2 expression is higher in Tibialis MNs compared to Gastrocnemius MNs suggesting a specific mGluR gene expression profile in these two MN pools. Finally, we assessed the functional impact of mGluR modulation on electrically-induced bouts of fictive locomotion in the isolated spinal cord preparation of P1-P3 mice, and in vivo during spontaneous episodes of swimming activity in both P1-P3 and P8-P12 mouse pups. We observed that the mGluR agonists induced distinct and specific effects on the motor burst amplitudes and period of the locomotor rhythms tested and that their actions are function of the developmental stage of the animals. Altogether our data show that the metabotropic glutamatergic system exerts a complex neuromodulation in the developing spinal lumbar motor networks and provide new insights into the expression and modulation of ADSP in MNs.